2015
DOI: 10.1016/j.gde.2015.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Genomic investigations of evolutionary dynamics and epistasis in microbial evolution experiments

Abstract: Microbial evolution experiments enable us to watch adaptation in real time, and to quantify the repeatability and predictability of evolution by comparing identical replicate populations. Further, we can resurrect ancestral types to examine changes over evolutionary time. Until recently, experimental evolution has been limited to measuring phenotypic changes, or to tracking a few genetic markers over time. However, recent advances in sequencing technology now make it possible to extensively sequence clones or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 91 publications
(65 reference statements)
1
47
0
Order By: Relevance
“…Epistasis is an important factor that can impose strong constraints on the adaptive process of bacterial populations [47,48]. This has been extensively studied in vitro [29,30,49,50] but only rarely in vivo [51].…”
Section: Discussionmentioning
confidence: 99%
“…Epistasis is an important factor that can impose strong constraints on the adaptive process of bacterial populations [47,48]. This has been extensively studied in vitro [29,30,49,50] but only rarely in vivo [51].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, considerable uncertainty surrounds the relative importance of the availability of adaptive mutations, pleiotropy and epistasis in constraining adaptive paths (Stern 2011;Storz 2018). One fruitful approach to addressing this question has been to examine repeated bouts of adaptation in microbial systems subject to a common selective pressure and identical starting conditions (Jerison and Desai 2015). Unfortunately, such approaches still have limited utility in multicellular eukaryotes and likely don't reveal the full range of constraints operating in nature.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies of pathogens [12], laboratory evolution experiments [13], and some environmental communities [14][15][16][17] have shown that microbial evolutionary dynamics are often dominated by rapid adaptation, with new variants accumulating within months or years [7,14,[18][19][20][21][22][23][24][25]. However, it is not clear how this existing picture of microbial evolution extends to a more complex and established ecosystem like the healthy gut microbiome.…”
Section: Introductionmentioning
confidence: 99%